If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -10x = 49 + -17x Solving 11 + -10x = 49 + -17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17x' to each side of the equation. 11 + -10x + 17x = 49 + -17x + 17x Combine like terms: -10x + 17x = 7x 11 + 7x = 49 + -17x + 17x Combine like terms: -17x + 17x = 0 11 + 7x = 49 + 0 11 + 7x = 49 Add '-11' to each side of the equation. 11 + -11 + 7x = 49 + -11 Combine like terms: 11 + -11 = 0 0 + 7x = 49 + -11 7x = 49 + -11 Combine like terms: 49 + -11 = 38 7x = 38 Divide each side by '7'. x = 5.428571429 Simplifying x = 5.428571429
| (2d)-(7)=(8)-(3d) | | 36-31x=-10x | | 3(6x+3)=15 | | -2(.25+.85)-3y=10 | | 6x+6=-120-8x | | 3x-4(x+1)+10=0 | | 2(-2+x)-(x-4)+4(1+x)=0 | | -14=-(2x+2) | | x^2-3x=-3 | | 1-5x= | | 3f*15=45 | | 112b+4.4c=1000 | | -12-5x=13-10x | | -4y+6=-8+3y | | 3(8-b)=27 | | b+26-32.9=15 | | 24=3(2-2x) | | 7x^2=50 | | 5d+10=25 | | rt-2n=y | | 25X^2-20X=9X^2+12X | | 95=5x | | 4x-17=-1 | | 5n+9=y | | 9x+3= | | 5d-35=90 | | 3.5+4.5= | | 2b-8=-b+7 | | 7f+g=5 | | 14x+x=30 | | 2a-15=31 | | 3x+9-6x-4=32 |